2018
DOI: 10.1177/2475530318788943
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Inhibition in a Patient With Psoriasis and Concurrent Vitiligo

Abstract: Background: Psoriasis and vitiligo are 2 autoimmune conditions that can occur concurrently in patients. At present, no single systemic therapy has been identified to be effective in treating both the conditions. Observations: Recent advances in our understanding of the T helper (Th) 17 subset of Th cells suggests that interleukin (IL)-17 may play a key role in the pathogenesis of both vitiligo and psoriasis. We report a case of anatomically superimposed psoriatic plaques and vitiligo for which treatment with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A recent single-arm pilot study demonstrated that upon anti-IL-17A treatment, there was neither clinical nor laboratory improvement in active vitiligo patients (Speeckaert et al, 2019). In another study, IL-17 blockade using ixekizumab in a patient of psoriasis suffering from vitiligo, there was some improvement observed initially; however, there was no improvement in the vitiligo condition of the patient in long-term follow-up (Katz et al, 2018). Interestingly, in our study, there was no significant difference in skin-homing or systemic Th17 cells (CD4 + IL-17 + IL-4 − IFNγ -IL-9 − ) in active vitiligo as compared to the healthy controls (Figure 2d).…”
Section: Significancementioning
confidence: 99%
“…A recent single-arm pilot study demonstrated that upon anti-IL-17A treatment, there was neither clinical nor laboratory improvement in active vitiligo patients (Speeckaert et al, 2019). In another study, IL-17 blockade using ixekizumab in a patient of psoriasis suffering from vitiligo, there was some improvement observed initially; however, there was no improvement in the vitiligo condition of the patient in long-term follow-up (Katz et al, 2018). Interestingly, in our study, there was no significant difference in skin-homing or systemic Th17 cells (CD4 + IL-17 + IL-4 − IFNγ -IL-9 − ) in active vitiligo as compared to the healthy controls (Figure 2d).…”
Section: Significancementioning
confidence: 99%
“…Thus, the authors were of the opinion that targeting the IL17/Th17 axis may not be effective in treating vitiligo. 46 In another pilot trial, 8 patients with active vitiligo were treated with secukinumab 300 mg at weeks 0, 1, 2, 3, 4, and subsequently every 4 weeks for 7 months and followed up for an Other 5 patients attained stability which was maintained at 6 months post-treatment but did not attain the primary target of attaining >50% repigmentation. Th17 pathway was correlated with active disease.…”
Section: Il 17/23 Inhibitorsmentioning
confidence: 99%
“…The psoriatic lesions responded with complete clearance at 59 weeks, whereas the vitiligo lesions showed no response and in fact, the progression continued with the appearance of new depigmented patches in previously uninvolved areas. Thus, the authors were of the opinion that targeting the IL17/Th17 axis may not be effective in treating vitiligo 46 …”
Section: Etiopathogenesis Of Vitiligomentioning
confidence: 99%